2012
DOI: 10.7314/apjcp.2012.13.9.4577
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer in Younger and Older Patients: Do We Treat Them Differently?

Abstract: Diagnostic and therapeutic strategies of prostate cancer may largely influenced by patients' age at presentation. This study is aimed to evaluate the characteristics, diagnostic and treatment strategies in prostate cancer patients in our centres. A cross-sectional analytic study of prostate cancer data in two main referral cancer centres, Cipto Mangunkusumo General Hospital and Dharmais National Cancer Centre from 1995-2010, was therefore performed. Patients were divided into 2 sub-populations; below 60 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Surgical or medical primary androgen deprivation therapy (PADT) is another option especially in elderly population. Situmorang et al (28) reported that 39% of clinical stage I-III patients older than 75 years received PADT compared with 10% of similar stage patients with age <60 years. Another study comparing localized and locally advanced cases treated with PADT found that the mean age was 74 and 68.07 years, respectively; 5-year OS was 77.3% in localized patients in contrast to 22.7% in locally advanced cases (29).…”
Section: Prostate Cancermentioning
confidence: 99%
“…Surgical or medical primary androgen deprivation therapy (PADT) is another option especially in elderly population. Situmorang et al (28) reported that 39% of clinical stage I-III patients older than 75 years received PADT compared with 10% of similar stage patients with age <60 years. Another study comparing localized and locally advanced cases treated with PADT found that the mean age was 74 and 68.07 years, respectively; 5-year OS was 77.3% in localized patients in contrast to 22.7% in locally advanced cases (29).…”
Section: Prostate Cancermentioning
confidence: 99%
“…In 18 of these, consideration of contra-indications could be considered not relevant, since they examined access to generic healthcare services (for example Burge et al examined access to palliative care among cancer patients [41]). However, in eight other studies, this omission makes interpretation problematic as non-receipt may or may not have been appropriate (for example Situmorang et al examined treatment for prostate cancer [42]). Thirteen studies included measures of comorbidity within their statistical analyses, but in eight of these no clear justification for their inclusion was provided.…”
Section: Resultsmentioning
confidence: 99%
“…As well the US Preventive Services Task Force (USPSTF) has recommended against routine PSA screening for prostate cancer and claimed upper limit of age as 75 in an earlier version (Moyer, 2012). However, this lack of clear guidance on this point is well reflected by the treatment practices of urologists which show a great variance (Lipinski et al, 2013;Situmorang et al, 2013;Verim et al, 2013). In our practice, PSA analysis in the elderly depends mainly on either physical examination and/or lower urinary tract symptom driven suggestion, or patient's own will as a continuum of yearly PSA screening.…”
Section: Discussionmentioning
confidence: 99%